Analisis Pengaruh Kemiskinan Terhadap Pertumbuhan Ekonomi di Provinsi D.I. Yogyakarta - Huwaida, Yumna; Fatimah, Astri; Muharani, Sabrina; Iraswati, Aisya; Desmawan, Deris (Jurnal Manajemen Akuntansi (JUMSI), 2023)
One indicator of a nation or region's progress and development is economic growth. A province's economic growth is a type of rising macroeconomic indicators. This study's goal is to examine the impact of poverty on economic development in DI Yogyakarta. The author employs online browsing, documentation studies, and library research tools to gather secondary data from relevant organizations, particularly the Central Bureau of Statistics (BPS) DI Yogyakarta. The study's findings indicate that poverty and unemployment do not significantly interact. It is uncertain if a decline in the unemployment rate would result in a reduction in poverty in the DI Yogyakarta Province.